Surfing with the tide: Real estate as a hedge against inflation - Malović Marko; Roganović Miloš (Trendovi u Poslovanju)
After a multi-year period of low interest rates and monetary expansions following the so-called great moderation, the issue of how to protect capital from value erosion became highly relevant once again. Recent notable increase in inflation re-woke theoretical and practical disagreements about what causes inflation in the first place, in which ways and to what extent inflation is being costly for both households and investors, and in particular how if at all households are able to protect their modest portfolios. Inflation undoubtedly erodes the value of corporate earnings as well as profits of financial intermediaries, thereby impacting virtually all asset classes and all kinds of investors. Nonetheless, it is usually the harshest on the receiving end, since predominantly households are most badly hit by inflation, especially those with fixed - or way too slowly adjusting incomes. Therefore, during a period of accelerated inflationary pressure, it becomes ever more important for all parties to obtain financial instruments that effectively protect capital from value erosion. The question arises of where to invest in order to at least preserve value i.e. keep up with the inflation rate in terms of investment returns. The aim of this research is to measure the correlation between real estate performance and inflation in order to determine whether this type of asset can be a good source of protection against inflation. Also, the aim of the paper is to compare the real estate protective potential against inflation with the performance of stocks, bonds and gold in conserving inherited purchasing power.